Immune-mediated blood-brain barrier disruption after ischemic stroke: mechanisms and therapeutic targets - Wang, Hanjing; Yiqiang, Zhang; Cai, Jie; Guo, Jiawei (Frontiers in Immunology, 2025)
Ischemic stroke is an acute cerebrovascular disorder characterized by the obstruction of cerebral arteries, leading to focal cerebral ischemia and infarction, ultimately resulting in neurological deficits. Its pathogenesis involves a cascade of immune-inflammatory responses and blood-brain barrier (BBB) disruption. Emerging evidence highlights that immune inflammation is a central driver of post-stroke brain injury. Microglial activation, neutrophil infiltration, and the release of pro-inflammatory cytokines collectively exacerbate BBB breakdown and neuronal death. Concurrently, these immune processes participate in tissue remodeling and repair. Notably, the interplay between immune-mediated inflammation and BBB damage forms a vicious cycle that aggravates neurological outcomes and hampers recovery. This review focuses on the molecular mechanisms of ischemia and hypoxia-induced BBB dysfunction, and the immunological processes involved, aiming to provide insights into multi-target and temporally precise neuroprotective strategies for ischemic stroke.